Analisis Norma dan Etika Pariwisata terhadap Kasus Penipuan Wisatawan di Kawasan Keraton Yogyakarta - Retno Moortrisari Widianingrum; Dwi Cahyono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
Yogyakarta Palace, a popular tourist attraction, is an easy target for scammers. As a result, tourists unfamiliar with the destination become victims. In this scam case, scammers in the Yogyakarta Palace area used their modus operandi, posing as tour guides and offering civet coffee without showing a price list. Norm violations and tourism ethics are the main focus of this study. A qualitative descriptive research method was used, with data collection through literature studies and both offline and online observations. Five informants were interviewed between December 2025 and February 2026. These five individuals included stakeholders from the Yogyakarta Palace, netizens who created information threads to avoid scams, and randomly selected tourists. Data obtained through interviews were analyzed narratively, analyzing data in the form of stories from informants. Furthermore, ethnographic analysis was used to examine the culture and social interactions within specific groups, in this case, tourism subjects in the Yogyakarta Palace area. This study concludes that the scam methods used by scammers, such as posing as tour guides and offering civet coffee without a price list, create discomfort and insecurity for tourists during their travel. Losses can also affect tourists and the tourist attractions targeted by the scam. Stakeholder responses in accordance with norms and the World Tourism Code of Ethics are crucial because they can prevent further scams and ensure tourists' safety and comfort while travelling. This research is expected to contribute to stakeholders by providing clear information on related tourist attractions and to increase awareness among tourists visiting the Yogyakarta Palace area.